Respiratory patterns in spontaneously breathing near-term lambs delivered by caesarean section under spinal anaesthesia - Davies, I. M.; Crossley, K. J.; McGillick, E. V.; Nitsos, I.; Rodgers, K.; Thiel, A.; Zahra, V. A.; te Pas, A. B.; Hooper, S. B. (Frontiers in Pediatrics, 2023)
The transition to newborn life has typically been studied in intubated and mechanically ventilated newborn lambs delivered via caesarean section (CS) under general anaesthesia. As a result, little is known of the spontaneous breathing patterns in lambs at birth, particularly those at risk of developing respiratory distress (RD). We have developed a method for delivering spontaneously breathing near-term lambs to characterise their breathing patterns in the immediate newborn period. At 137-8 days gestation (2-3 days prior to delivery; term ~147 days), fetal lambs (n=7) were partially exteriorised for instrumentation (insertion of catheters and flow probes) before they were returned to the uterus. At 140 days, lambs were delivered via CS under light maternal sedation and spinal anaesthesia. Lambs were physically stimulated and when continuous breathing was established, the umbilical cord was clamped. Breathing patterns were assessed by measuring intrapleural and upper-tracheal pressures during the first four hours after birth. Newborn lambs display significant heterogeneity in respiratory patterns in the immediate newborn period that change with time after birth. Seven distinct breathing patterns were identified including: i) quiet (tidal) breathing, ii) breathing during active periods, iii) breathing during oral feeding, iv) tachypnea, v) expiratory braking manoeuvres, vi) expiratory pauses or holding, and vii) step changes in ventilation. We have described normal respiratory behaviour in newborn lambs, in order to identify respiratory behaviours that are indicative of RD in term newborn infants.